Experimental study on stress and deformation characteristics of foundation pit considering excavation width using 3D printing technology - Liu, Fengzhou; Zhang, Xu; Xiang, Maolong; Lyu, Jingkang; Feng, Rui; LIU, Shouhua (Frontiers in Earth Science, 2024)
A sophisticated model of the foundation pit support structure was developed via a model test that incorporated 3D printing technology. A meticulously scaled-down simulation of foundation pit excavation was conducted, utilizing the excavation width of the foundation pit as the sole variable, to evaluate and compare the impact of various foundation pit widths on the force and deformation characteristics of the foundation pit following layer-by-layer excavation. The findings indicate that the stress and deformation characteristics of the retaining structure shift from the "cantilever" mode to a composite mode of "internally convex" or "concave-convex" as the pit is excavated and internal support is installed. The change in pit width has minimal influence on the mechanical response law of the support structure during excavation. Nonetheless, the alteration in the pit width had a direct effect on both the internal force and deformation of the support structure, as well as the change in surface settlement value. In the experiment, wider pits had monitoring values that increased multiple times compared to narrower pits. The width of the foundation pit has a considerable impact on the mechanical response and stability of the pit, which is evident in the relatively lower lateral earth pressure on the outside of the retaining structure in narrower pits. This results in less stress and deformation of the pit structure. Moreover, the decrease in the passive zone of the pit contributes to better stability, indicating that the lower lateral earth pressure on the outside of the retaining structure is an innate reason for the excellent stability of narrower pits.